Validation of the Caregiver Skills (CASK) scale in Catalonia: Concordance between caregivers in attitudes and behaviours. (14th June 2018) - Vintró‐Alcaraz, Cristina; Mestre‐Bach, Gemma; Steward, Trevor; Lozano‐Madrid, María; Agüera, Zaida; Jiménez‐Murcia, Susana; Pedraza, Anna M.; Serrano‐Troncoso, Eduardo; Ortiz García, Ana E.; Rangil, Teresa; Lorán, Eulalia; Soriano‐Pacheco, Jose; et al.
Abstract: Objective: The aim of this study was to validate a Spanish version of the Caregiver Skills scale (CASK) in a sample of eating disorder (ED) caregivers. A further aim was to examine the concordance/discrepancy between them (namely, between the mothers and fathers of ED patients). Method: Two hundred sixty‐five ED caregivers were recruited from ED centers in Catalonia, Spain. Confirmatory factor analyses was used to test the factorial structure of the CASK scale. Cronbach's α was used to measure internal consistency of the CASK scales. A comparison of the CASK measures between respondents (mothers and fathers) was conducted using generalized estimating equations. Results: Confirmatory factor analysis of the Spanish version of the CASK corroborated the strong factorial validity of the 6 factors of the original CASK questionnaire. Mothers and fathers did not differ significantly on CASK overall and subscale scores. There was however less concordance between parents on the bigger picture ( ICC  = 0.28) and biting your tongue ( ICC  = 0.08) subscales. Conclusions: The CASK is a valid tool to assess ED‐related attitudes in Spanish‐speaking caregivers. Furthermore, caregivers and patients alike could stand to benefit from interventions focused on improving areas such as ED beliefs, effective communication, quality of life, and emotional distancing.